2020
DOI: 10.2478/fhort-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Thrips (Thysanoptera) associated with onion (Allium cepa L.) and Welsh onion (Allium fistulosum L.)

Abstract: We determined the abundance, species composition, sex ratio and seasonal dynamics of thrips on one cultivar of Welsh onion (Allium fistulosum) and eight cultivars of onion (Allium cepa) in South Poland within three vegetation seasons (2014–2016). Nine species of Thysanoptera were identified on A. cepa and A. fistulosum. Irrespective of the onion cultivar, Thrips tabaci was the dominant species (64.4% of all collected thrips specimens), while Frankliniella intonsa also occurred in high numbers (28.3%). Converse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…We found that the main species of thrips that affects onion and its related species is Thrips tabaci , which is in agreement with previous studies [ 5 , 29 , 41 , 42 ]. Other thrips species such as Thrips palmi , Scirtothrips dorsalis , Frankliniella tenuicornis , Frankliniella intonsa , and Frankliniella occidentalis , were present at specific locations.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We found that the main species of thrips that affects onion and its related species is Thrips tabaci , which is in agreement with previous studies [ 5 , 29 , 41 , 42 ]. Other thrips species such as Thrips palmi , Scirtothrips dorsalis , Frankliniella tenuicornis , Frankliniella intonsa , and Frankliniella occidentalis , were present at specific locations.…”
Section: Discussionsupporting
confidence: 93%
“…intonsa at Sansai might be associated with the presence of Allium fistulosum in the Allium spp field since it has been reported as the common host plant for F . intonsa [ 29 ]. Apart from that, the Allium field in Sansai was surrounded by several (crop) species, including banana, bamboo, and herbs such as marigold and weeds, from which thrips may have moved into the field.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations